2016
DOI: 10.1038/leu.2016.162
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies highly recurrent somatic GATA2 and CEBPA mutations in acute erythroid leukemia

Abstract: Acute erythroid leukemia (AEL), characterized by a predominant erythroid proliferation, is a subtype of acute myelogenous leukemia. The genetic basis of AEL remains poorly defined. Through whole-exome sequencing, we identified high frequencies of mutations in CEBPA (32.7%), GATA2 (22.4%), NPM1 (15.5%), SETBP1 (12.1%) and U2AF1 (12.1%). Structure prediction analysis revealed that most of the GATA2 mutations were located at the DNA-binding N-terminal zinc-finger near the DNA-binding interface, suggesting that mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 31 publications
4
44
0
Order By: Relevance
“…Mutations in the DNA binding C-terminal zinc finger inhibit binding (Hahn et al, 2011), while +9.5 enhancer mutations reduce GATA2 expression (Hsu et al, 2013; Johnson et al, 2012). Mutations also occur in the N-terminal zinc finger that is not required for DNA binding (Ping et al, 2017). GATA-2 promotes AML cell proliferation (Katsumura et al, 2016) and mediates leukemogenic activity in a mouse model involving Tet2 deficiency and mutant Flt3(ITD) expression (Shih et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the DNA binding C-terminal zinc finger inhibit binding (Hahn et al, 2011), while +9.5 enhancer mutations reduce GATA2 expression (Hsu et al, 2013; Johnson et al, 2012). Mutations also occur in the N-terminal zinc finger that is not required for DNA binding (Ping et al, 2017). GATA-2 promotes AML cell proliferation (Katsumura et al, 2016) and mediates leukemogenic activity in a mouse model involving Tet2 deficiency and mutant Flt3(ITD) expression (Shih et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They detected GATA2 mutations in 5.5% of non-AEL AML and in 15% of CML in blast crisis and reported that the frequency of GATA2 mutations in AEL (22.4%) is significantly higher than in non-AEL AML. 24 Iacobucci et al confirmed that these data with a cohort of 159 child and adult AEL cases presenting a mutational prevalence of 14.4%. 26 Tien et al analyzed GATA2 mutations in non-M3 AML patients and identified 44 GATA2 mutations in 43 (6.2%) of their 693 patients, two-thirds of those mutations located in the ZF1 domain.…”
Section: Gatazf Mutations: Incidence and Clinical Correlations In Hmentioning
confidence: 74%
“…The authors did not observe such a dominant‐negative effect in ZF1 mutants P304H and L321P. Additionally, in their study, the overexpression of GATA2 mutants in the mouse myeloid progenitor cell line 32D had no effect on proliferation or colony‐forming ability …”
Section: Gata2 Zf Mutations: Functional Implicationsmentioning
confidence: 85%
See 2 more Smart Citations